Perancangan Kantor Dinas Pendidikan Pemuda Dan Olahraga Kabupaten Sikka Dengan Pendekatan Arsitektur Post-Moderen - Dede, Petrus Jhon Alfred Depa (Program Studi Teknik Sipil dan Program Studi Arsitektur Fakultas Sains & Teknologi Universitas Flores, 2022)
The building of youth education office and sport of Sikka District is currently located in the Nasiona l Housing complex on Jalan Mawar. This Kantor building has a simple building and only one floor. The area of the location is very small and there are minimal supporting facilities. In addition, this office is also locatedin a residential area with a fairly high density. Based on the author's initial observations and studies, it needs to be proposed to be relocated to a new place, namely on Eltari Street. The reason for choosing the location with consideration is that the location is the office area of the Sikka Regency Government. Thus, it can facilitate and optimize access to services and relationships between government offices. The planning and design of this office is expected to reflect the fusion and mixing of local architectural values with today's architecture. Therefore, the selection and approach used as a design concept is Post-Modern Architecture.This method in designing is carried out by analyzing the data by means of; 1). quantitative analysis, 2). qualitative analysis, and 3). comparative analysis. Data collection is carried out in the following ways; 1). literature study, 2). interviews, 3). observation. Post-Modern Architecture applied to the concept of designis; a). mcontaining elements of communication that are local or popular, b). urban context, c). metaphorical form, d). is eclectic, e). reflects general aspirations, and f). reapply the technique of ornamentation.